A Qualitative Study of Factors Influencing Initiation and Adherence to Micronutrient Supplementation Among Women of Reproductive Age in Vietnam. (December 2016) - Nechitilo, Meredith; Nguyen, Phuong; Webb-Girard, Amy; Gonzalez-Casanova, Ines; Martorell, Reynaldo; DiGirolamo, Ann; Ramakrishnan, Usha
Background and objectives: Initiation and adherence are both critical challenges for micronutrient supplementation programs, especially during the preconceptional period. This study examines factors influencing initiation of supplement use and continued adherence among women participating in PRECONCEPT, a double-blind randomized controlled trial of preconception micronutrient supplementation. Methods: In-depth interviews were conducted with 39 participants during different periods (prepregnancy [n = 15], pregnancy [n = 8], postpartum [n = 8], and dropouts [n = 8]). We examined participants' knowledge about nutritional needs and micronutrient deficiencies, individual experience with nutritional supplements, and perceived benefits and side effects of supplements. Four focus groups were conducted with 24 village health workers (VHWs) to collect information on VHWs' perceptions of factors influencing participants' adherence and logistics of supplement distribution. Influences on initiation and adherence were examined within the Health Belief Model framework. Results: Primary barriers to initiation of supplement use were low perceptions of severity of nutrient deficiencies and personal susceptibility. These are associated with low knowledge and awareness around deficiencies. Perceived seriousness and susceptibility varied by nutrient: high for iron during pregnancy but low for all other micronutrient deficiencies, including iron outside pregnancy. Continued maintained adherence to an initiated regimen was influenced by the woman's perceptions of the health benefits of, and barriers to, regular supplement use. Conclusion: Initiation of supplement use was influenced by perceived susceptibility and severity of nutrient deficiencies, while maintained adherence to consistent use was influenced by perceived benefits and barriers. Recognizing the influences on each stage may help improve adherence and maximize positive effects of future interventions.